2016
DOI: 10.1002/pbc.25874
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Factor VIII Inhibitor Titers During Immune Tolerance Induction With Recombinant Factor VIII-Fc Fusion Protein

Abstract: The development of inhibitors toward factor VIII (FVIII) is a common and serious complication of hemophilia A (HA) therapy. Patients with hemophilia who develop inhibitors often undergo time- and resource-intensive immune tolerance induction (ITI) protocols. We report a 15-month-old male with severe HA and a high-titer inhibitor that occurred while receiving prophylactic treatment with recombinant FVIII (rFVIII), in whom significant inhibitor titer reduction was achieved with thrice weekly infusions of a new, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…In addition, epitopes in the Fc fragment are known to upregulate regulatory T cells, which can result in tipping the balance towards tolerance over immunogenicity . These data are consistent with prior case reports in which 4 patients had been successfully treated with rFVIIIFc for inhibitors and with the case series described here.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, epitopes in the Fc fragment are known to upregulate regulatory T cells, which can result in tipping the balance towards tolerance over immunogenicity . These data are consistent with prior case reports in which 4 patients had been successfully treated with rFVIIIFc for inhibitors and with the case series described here.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that rFVIIIFc could reduce inhibitor titers in inhibitor-positive HemA patients in recent case reports. 11,12 In addition, a retrospective chart review reported that rFVIIIFc achieved rapid time to tolerization in high-risk first-time ITI patients. 13 In preclinical animal studies, decreased levels of inhibitor formation after rFVIIIFc treatment of HemA mice was reported, compared with rFVIII treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The recent fusion of FVIII with a human IgG 1 Fc has created a therapeutic FVIII with extended half-life due to recycling of the protein via the neonatal Fc receptor (FcRn) (143). Initial pre-clinical and clinical studies (144)(145)(146)(147) have suggested that FVIII-Fc may also lower the incidence of inhibitor development and increase ITI success rates (148). A recent study based on retrospective chart review indicated that patients receiving FVIII-Fc for ITI tolerized faster than with standard ITI protocols utilizing non-Fc fusion products, and several patients receiving "rescue ITI, " i.e., who had failed an earlier ITI regimen, became tolerized during ITI with FVIII-Fc and were able to resume standard replacement therapy (149).…”
Section: Fviii-fc Fusion Proteinsmentioning
confidence: 99%